Alexithymia and Psychopathology in Patients Suffering From Inflammatory Bowel Disease: Arising Differences and Correlations to Tailoring Therapeutic Strategies - Viganò, Caterina A.; Beltrami, Marta M.; Bosi, Monica F.; Zanello, Riccardo; Valtorta, Marta; Maconi, Giovanni (Frontiers in Psychiatry, 2018)
Comorbidity with anxiety or depression is common in patients with Inflammatory Bowel Disease (IBD) as Crohn Disease (CD) and Ulcerative Colitis (UC). Data suggest that the cognitive construct of alexithymia has high prevalence in people suffering from anxiety and mood disorders and even in people with IBD. Most studies have investigated mainly anxiety and depression, considering IBD population as a homogeneous group of patients. Little evidence shows the impact of alexithymia on the course of IBD. We evaluated a broad spectrum of psychopathological symptoms and alexithymia levels in a group of outpatients affected by IBD in clinical remission, comparing CD and UC and investigating the relationship with clinical and socio-demographic variables. 170 IBD outpatients were screened by using the Hospital Anxiety Depression Scale (HADS), the Self-report Symptom Inventory-90-Revised (SCL-90-R) and the Toronto Alexithymia Scale (TAS-20). A high prevalence of anxious and depressive symptoms (42.35% and 25.8% respectively) together with alexithymia (31.76%) was confirmed. CD patients experienced high levels of depression (HADS Depression 33.8% p=0.034; SCL-90-R mean 1.39 p<0.001), somatisation (SCL-90-R mean 1.04 p<0.001), obsessive-compulsive symptoms (SCL-90-R mean 1.2 p<0.001) and global severity (SCL-90-R mean 1.15 p<0.001). There is no statistical difference in the prevalence of alexithymia in both subpopulations. The levels of alexithymia are correlated to the levels of anxiety (HADS Anxiety rs=0.516 p<0.001), depression (HADS Depression rs=0.556 p<0.001; SCL-90-R rs=0.274 p=0.001), somatisation (SCL-90-R rs=0.229 p=0.005), obsessive-compulsive symptoms (SCL-90-R rs=0.362 p<0.001) and global severity (SCL-90-R rs=0.265 p=0.001). Furthermore, alexithymia is associated with a delay of diagnosis of IBD, poly-therapies and greater IBD extension. Older age, female gender, greater IBD extension, surgery and delay of diagnosis seem to be related to a high prevalence of psychopathological symptoms such as anxiety, depression, somatisation and obsessive-compulsive symptoms. Psychopathological symptoms and high levels of alexithymia are frequent in IBD patients and seem to be related to a high risk of poor clinical outcome. CD patients could be considered at higher risk of mental comorbidity. A more comprehensive psychiatric assessment, including alexithymia, and an integrated treatment of underlying conditions, must be taken into account in order to improve the global prognosis of the disease.